Risk Factors for Stunting in Toddlers in Gowa Regency - Sukmawati Sukmawati; Adriyani Adam; Sirajuddin Sirajuddin; Nadimin Nadimin; Nurhidayah Tiasya Sanas (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Stunting is a nutritional problem faced in various parts of the world, especially in poor countries and developing countries. Prevalence of Stunting in Indonesia based on the results of the Indonesian Nutrition Status Study (SSGI) in 2019 was 27.7% and in 2021 it was 24.4%.  In South Sulawesi, the prevalence of Stunting based on SSGI results in 2021 is 27% while the prevalence of Stunting in Gowa Regency is 33%. The Objectives of this study to Investigating the correlation between stunting and parenting, nutrient intake, infectious diseases, and environmental sanitation.  This research method is observational and analytical with a case-control research design. The number of samples was 38 consisting of 19 working toddler mothers who had Stunting toddlers as a case group and 19 working toddler mothers who had non-Stunting toddlers as a control group. Research results show a foster-pattern connection with Stunting (p= 0,012), there is a connection between protein nutrient intake and stunting (p= 0,020), there is a connection between fat nutrient intake and stunting (p= 0,017), there is a connection between carbohydrate nutrient intake and stunting (p= 0,007). It was concluded that the Stunting incident in toddlers aged 24 to 59 months was related to foster patterns and nutritional substance intake but was not related to infectious diseases and environmental sanitation.